The passional world of Marina Colsanti, in "A moça tecelã" - Maia, Mara Jane Sousa (Laboratório Editorial FCL-UNESP, 2008)
This study aims to examine the course of passions in the story "A moça tecelã", by Marina Colasanti. We apply some theoretical proposals of the French semiotics, including the tensivity as a tool to seize the meaning effects of modal, aspectual and structural qualifications that change the affected subject by the passion.